2018
DOI: 10.11622/smedj.2018036
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, activity and fatigue reported by Postgraduate Year 1 residents: a prospective cohort study comparing the effects of night float versus the traditional overnight on-call system

Abstract: The physical activity and amount of sleep of residents on night-float and on-call rota were not significantly different. Residents on night-float reported comparatively higher fatigue and burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 11 publications
6
22
1
Order By: Relevance
“…Our study, showed that NF system had signi cant improvement in these three aspects. Several studies showed the traditional on-call system is associated with loss of sleep and fatigue which is like our study results [2][3]. Furthermore, the 24 hour on-call system shown to negatively affect physical function and memory in our pediatric residents and neurosurgery residents in another study [15].…”
Section: Discussion and Literature Reviewsupporting
confidence: 82%
See 3 more Smart Citations
“…Our study, showed that NF system had signi cant improvement in these three aspects. Several studies showed the traditional on-call system is associated with loss of sleep and fatigue which is like our study results [2][3]. Furthermore, the 24 hour on-call system shown to negatively affect physical function and memory in our pediatric residents and neurosurgery residents in another study [15].…”
Section: Discussion and Literature Reviewsupporting
confidence: 82%
“…In addition, a study suggested minimizing work hours and assigning health care workers to speci c rules in order to prevent physician burnout [16]. Moreover, a survey advised a time off to improve residents' well-being as it showed that long duty hours could cause residents burnout which can cause depression, substance abuse, and suicide attempt [2][3]5].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to ensure the welfare of residents as well as patient safety in this environment, several institutions have adopted a night float on-call system. The impact of a night float compared Singapore: what does the future hold? with the traditional overnight on-call system has been studied by Low et al (11) in relation to the sleep quality and fatigue rates of residents, with some surprising results. It is clear that we will have to work out a system that protects both patients and trainees from fatigued residents while ensuring optimal clinical training in a complex environment.…”
mentioning
confidence: 99%